Imidazole Derivatives as Potential Therapeutic Agents - Sharma, Archana; Kumar, Vipin; Kharb, Rajeev; Kumar, Sunil; Chander Sharma, Prabodh; Pal Pathak, Dharam (Current Pharmaceutical Design, 2016)
Background: The imidazole nucleus is inimitable and ubiquitous and it is very well known to play an important role in living organisms. Imidazole derivatives are under intensive scientific exploration due to their diverse and significant pharmacological activities. Methods: The present paper is an attempt to discuss chemistry, synthetic aspects including click chemistry procedures of imidazoles through systematic literature survey. Results: Biological activity profiles of the imidazole derivatives reported in recent scientific literature from 2000 to 2015 have been discussed in detail. It has been found that imidazole derivatives depict appreciable antiinfective activity potential. Conclusion: It is anticipated that the information compiled in this paper will be useful and motivating to prospective researchers working on this heterocylic scaffold.
Keywords: click chemistry